Unraveling inflammation’s role in cerebral aneurysm recanalization: A comprehensive systematic review - Amran, Muhammad Yunus; Gunadi, Siti Giranti Ardilia; Fitrah, Yusran Ady; Pasereng, Brigita Dian; Syahfitri, Evira (Acta Biomedica Atenei Parmensis, 2025)
Background: Although significant progress has been made in identifying risk factors for cerebral aneurysms (CAs), the exact pathological mechanisms responsible for aneurysm recurrence remain poorly elucidated. Inflammation has increasingly been implicated in the progression and recurrence of aneurysms following endovascular coiling. This systematic review aims to evaluate the role of inflammatory factors in post-coiling recanalization across intracranial aneurysms based on literature from the last decade. Methods: The review was conducted in accordance with PRISMA 2020 guidelines. English-language studies published between 2015 and 2025 were retrieved using PubMed, SpringerLink, SagePub, and Google Scholar. Editorials, review articles, duplicate publications, and studies lacking a digital object identifier (DOI) were excluded. Articles were screened through a three-step process (title, abstract, and full-text review). Results: A total of 1,800 records were identified through database searches. After applying inclusion and exclusion criteria and conducting full-text analysis, seven eligible studies were included. The selected literature reported on inflammatory mediators such as tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), matrix metalloproteinase (MMP-2) and MMP-9, macrophage subtypes, and complement system activation. These factors were associated with impaired thrombus stabilization, delayed endothelial repair, and increased likelihood of CA recanalization. Conclusion: Inflammatory responses are key contributors to aneurysm recurrence following coiling, acting through vessel wall degradation, extracellular matrix remodeling, and endothelial dysfunction. Macrophage infiltration, cytokine upregulation, MMP activation, and complement involvement are mechanistically linked to long-term instability of treated aneurysms. Future research should explore anti-inflammatory adjunct therapies, optimize biomaterial selection, and identify predictive inflammatory biomarkers to enhance the durability of endovascular aneurysm treatment. (www.actabiomedica.it)